Koli women organizers of the festival - Mumbai Archive Project Team (Jio Institute, 2024)
The Versova Koli Seafood Festival is an opportunity to connect with members of the Koli community, including fishermen, fisherwomen, artisans, and cultural performers, to learn about their way of life, occupations, and cultural practices.